SIRT7 restricts HBV transcription and replication through catalyzing desuccinylation of histone H3 associated with cccDNA minichromosome - Yu, Hai-Bo; Cheng, Sheng-Tao; Ren, Fang; Chen, Yong; Shi, Xiao-Feng; Wong, Vincent Kam Wai; Law, Betty Yuen Kwan; Ren, Ji-Hua; Zhong, Shan; Chen, Wei-Xian; Xu, Hong-Mei; Zhang, Zhen-Zhen; et al. (Clinical science (1979), 2021)
Chronic hepatitis B virus (HBV) infection is a significant public health burden worldwide. HBV covalently closed circular DNA (cccDNA) organized as a minichromosome in nucleus is responsible for viral persistence and is the key obstacle for a cure of chronic hepatitis B (CHB). Recent studies suggest cccDNA transcription is epigenetically regulated by histone modifications, especially histone acetylation and methylation. In the present study, we identified transcriptionally active histone succinylation (H3K122succ) as a new histone modification on cccDNA minichromosome by using cccDNA ChIP-Seq approach. Silent mating type information regulation 2 homolog 7 (SIRT7), as an NAD+-dependent histone desuccinylase, could bind to cccDNA through interaction with HBV core protein where it catalyzed histone 3 lysine 122 (H3K122) desuccinylation. Moreover, SIRT7 acts cooperatively with histone methyltransferase, suppressor of variegation 3–9 homolog 1 (SUV39H1) and SET domain containing 2 (SETD2) to induce silencing of HBV transcription through modulation of chromatin structure. Our data improved the understanding of histone modifications of the cccDNA minichromosome, thus transcriptional silencing of cccDNA may represent a novel antiviral strategy for the prevention or treatment of HBV infection.